LTE Network Optimization in Nagari Ulakan and Tapakis, Ulakan Tapakis District, Padang Pariaman Regency - Nugraha Saputra; Zurnawita Zurnawita; Firdaus Firdaus (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
This study aims to optimize the Long Term Evolution (LTE) network in Nagari Ulakan and Nagari Tapakis. The development of mobile telecommunications technology requires improvements in network coverage quality to accommodate increasing user demand and the need for high-speed, reliable data services. Challenges arise due to complex geographical and demographic conditions, which cause signal weaknesses (bad spots) that interfere with service quality. The methodology involves collecting performance data through drive tests using G-Net Track Pro, collecting parameters such as Reference Signal Received Power (RSRP), Reference Signal Received Quality (RSRQ), and Signal to Interference Noise Ratio (SINR) from XL Axiata (AXIS). The data was then analyzed to identify performance deficiencies. Network optimization was performed through Automatic Cell Planning (ACP) using Atoll software, enabling better coverage efficiency without the need for significant infrastructure expansion. The results showed significant improvements in key signal quality parameters, especially in previously problematic areas, after applying optimization techniques.